The Oxford handbook of the South African economy - Oqubay, Arkebe,; Tregenna, Fiona,; Valodia, Imraan, (Oxford handbooks online., 2021)
While sharing some characteristics with other middle-income countries, South Africa is a country with a unique economic history and distinctive economic features. It is a regional economic powerhouse that plays a significant role, not only in southern Africa and in the continent, but also as a member of BRICS. However, there has been a lack of structural transformation and weak economic growth, and South Africa faces the profound triple challenges of poverty, inequality, and unemployment. Any meaningful debate about economic policies to address these challenges needs to be informed by a deep understanding of historical developments, robust empirical evidence, and rigorous analysis of South Africa's complex economic landscape. This volume seeks to provide a wide-ranging set of original, detailed, and state-of-the-art analytical perspectives that contribute to scientific knowledge.